FAIR VALUE IN FINANCIAL REPORTS- IMPACT OF VALUATION AND REVALUATION A CASE STUDY - PUȚAN ALINA; DREGHICIU ANDREEA ELENA (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie)
In order to highlight the relationship between the relevant valuation, the preparation of financial reports that reflect reality and the influence on decisions is based on the main objective pursued by the preparation of financial reports, that reflecting the true picture;the true picture can only be achieved under the conditions in which the elements of the entity are subjected to a relevant valuation process, respectively revaluation. Based on these reports, different categories of users make various decisions with impact, both at a microeconomic and macroeconomic level. The true picture of the financial position and performance achieved with fair value of all patrimonial elements allows investors to assess risk and decide on investment opportunities, as well as raising capital, the entity's managers can carry out strategic planning and set realistic and sustainable goals, creditors can determine the entity's ability to honor its obligations, increases the confidence of employees and business partners. Correct reporting ensures compliance with financial and tax regulations, preventing penalties or reputational losses.